Paired-Pulse Parietal-Motor Stimulation Differentially Modulates Corticospinal Excitability across Hemispheres When Combined with Prism Adaptation. (22nd June 2016) - Schintu, Selene; Martín-Arévalo, Elisa; Vesia, Michael; Rossetti, Yves; Salemme, Romeo; Pisella, Laure; Farnè, Alessandro; Reilly, Karen T.
Abstract : Rightward prism adaptation ameliorates neglect symptoms while leftward prism adaptation (LPA) induces neglect-like biases in healthy individuals. Similarly, inhibitory repetitive transcranial magnetic stimulation (rTMS) on the right posterior parietal cortex (PPC) induces neglect-like behavior, whereas on the left PPC it ameliorates neglect symptoms and normalizes hyperexcitability of left hemisphere parietal-motor (PPC-M1) connectivity. Based on this analogy we hypothesized that LPA increases PPC-M1 excitability in the left hemisphere and decreases it in the right one. In an attempt to shed some light on the mechanisms underlying LPA's effects on cognition, we investigated this hypothesis in healthy individuals measuring PPC-M1 excitability with dual-site paired-pulse TMS (ppTMS). We found a left hemisphere increase and a right hemisphere decrease in the amplitude of motor evoked potentials elicited by paired as well as single pulses on M1. While this could indicate that LPA biases interhemispheric connectivity, it contradicts previous evidence that M1-only MEPs are unchanged after LPA. A control experiment showed that input-output curves were not affected by LPA per se . We conclude that LPA combined with ppTMS on PPC-M1 differentially alters the excitability of the left and right M1.